Heralded generation of an atomic NOON state - Chen, Yu-Ao; Bao, Xiao-Hui; Yuan, Zhen-Sheng; Chen, Shuai; Zhao, Bo; Pan, Jian-Wei (Physical review letters, 2010)
We report the heralded generation of an atomic NOON state by observation of phase super resolution in a motion-sensitive spin-wave (SW) interferometer. The SW interferometer is implemented by generating a superposition of two SWs and observing the interference between them, where the interference fringe is sensitive to the atomic collective motion. By heralded generation of a second order NOON state in the SW interferometer, we observe the interference pattern which provides strong evidence of phase super resolution. The demonstrated SW interferometer can in principle be scaled up to a highly entangled state, and thus is of fundamental importance, and might be used as an inertial sensor.
Gesehen am 07.03.2023